Regulatory T Cells Inhibit T Cell Activity by Downregulating CD137 Ligand via CD137 Trogocytosis - Khang Luu; Mugdha Vijay Patwardhan; Qun Zeng; Stina L. Wickström; Andreas Lundqvist; Herbert Schwarz (Cells, 2021)
CD137 is a costimulatory molecule expressed on activated T cells. CD137 ligand (CD137L) is expressed by antigen presenting cells (APC), which use the CD137—CD137L system to enhance immune responses. It was, therefore, surprising to discover CD137 expression on regulatory T cells (Treg). The function of CD137 in Treg are controversial. While some studies report that CD137 signalling converts Treg to effector T cells (Teff), other studies find that CD137-expressing Treg display a stronger inhibitory activity than CD137- Treg. Here, we describe that CD137 on Treg binds to CD137L on APC, upon which one of the two molecules is transferred via trogocytosis to the other cell, where CD137—CD137L forms a complex that is internalized and deprives APC of the immune-stimulatory CD137L. Truncated forms of CD137 that lack the cytoplasmic domain of CD137 are also able to downregulate CD137L, demonstrating that CD137 signalling is not required. Comparable data have been obtained with human and murine cells, indicating that this mechanism is evolutionarily conserved. These data describe trogocytosis of CD137 and CD137L as a new mechanism employed by Treg to control immune responses by downregulating the immunostimulatory CD137L on APC.